Predictive Value of EuroSCORE II in a Nepalese Tertiary University Hospital – Prospective Observational Study - Bashyal, Krishnaprasad; Baral, Ravi Kumar; Bhattarai, Anil; Khakural, Prabhat; Kadel, Prashiddha B.; Koirala, Bhagawan (Nepalese Heart Journal, 2023)
Background and Aims: The European System for Cardiac Operative Risk Evaluation (EuroSCORE) is an important tool for risk stratification in cardiac surgery. Updated EuroSCORE II (ESC II) is widely regarded as essential for risk stratification and several studies validate its efficacy, but these are fewer in Southern Asia and none in Nepal. Aim of this study was to compare the predicted versus observed early mortality in adults undergoing major cardiac surgeries in Nepalese population. Methods: A prospective observational study was conducted from September 2019 to May 2021 at Manmohan Cardiothoracic Vascular and Transplant Center. Calibration and discrimination of scoring system were main parameters analyzed in total sample and subgroups. Discrimination were observed by plotting receiver operating characteristic (ROC) curves and calculating area under curve (AUC). Two sample t test, McNemar’s test, Fisher’s exact t test and Chi square test were used to derive P value. Results: In this study, 249 patients were evaluated. Poor mortality prediction was shown by statistically significant p value <0.05 across all surgical groups. AUC for total cases, CABG and valve surgeries were 0.835, 0.766, 0.82 respectively. Conclusion The present study underpredicted mortality but displayed good discrimination for overall cardiac surgeries, with excellent discrimination in valve surgeries. As current sample is not entirely comparable to parent study, weak calibration could be attributed to it as etiology was mostly rheumatic with poorer cardiopulmonary reserve in this study versus degenerative etiology in original study.